Isothermal and Kinetic Investigation of Exploring the Potential of Citric Acid-Treated Trapa natans and Citrullus lanatus Peels for Biosorptive Removal of Brilliant Green Dye from Water - Muhammad Sadiq Hussain; Rabia Rehman; Muhammad Imran (Journal of Chemistry)
Trapa natans peels (TNPs) and Citrullus lanatus peels (CLPs) were utilized for the biosorptive removal of brilliant green dye (BGD), after modifying with citric acid. Characterization and surface morphology were studied by Fourier transform infrared spectroscopy and scanning electron microscopy. For the removal of BGD by citric acid-treated Trapa natans peels (CA-TNPs), the optimum conditions were obtained with adsorbent dose 0.8 g, contact time 25 minutes, initial pH 5, temperature 30°C, and agitation speed 100 rpm, while for the citric acid-treated Citrullus lanatus peels (CA-CLPs), adsorbent dose 0.8 g, contact time 20 minutes, pH 5, temperature 30°C, and agitation speed 100 rpm gave optimum results. The qmax values obtained were 108.6, 128, 144.9, and 188.68 mg/g for R-TNP, CA-TNP, R-CLP, and CA-CLP, respectively, while the correlation coefficient (R2) values obtained were 0.985, 0.986, 0.985, and 0.998 for R-TNP, CA-TNP, R-CLP, and CA-CLP, respectively. These favor the Langmuir isotherm and pseudo-second-order kinetics, with negative (ΔG0) values of all adsorbents, determining that the adsorption phenomenon is exothermic and spontaneous in nature. Both citric acid-treated peels of Trapa natans and Citrullus lanatus were found suitable for bulk-scale eradication of hazardous, toxic, and carcinogenic basic cationic dyes.